2021
DOI: 10.1088/1612-202x/ac0e3f
|View full text |Cite
|
Sign up to set email alerts
|

Influence of silver nanoparticles on the spectral-luminescent and lasing properties of merocyanine dyes solutions

Abstract: The effect of silver nanoparticles (NPs) on spectral-luminescent and generation properties of ethanol solutions of vinylogous series neutral merocyanine dye has been studied. Adding silver NPs to dye solutions has led to a growth of optical density D and fluorescence intensity I FL of the dye molecules. With lengthening of a polymethine chain the silver NPs' effect on the D and I IFL values has been increasing. Whilst, a spectral overlap between the silver NPs and merocyanines has been decreasing. It is argued… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…[43][44][45][46][47] Among these OSMs, ionic cyanine dyes are extensively utilized in biomedical applications due to their exceptional photophysical properties including high extinction coefficient, intense NIR fluorescence, and excellent biocompatibility, attributed to their extensive conjugation structures involving two delocalized charged nitrogen atoms and polymethine chains. [48][49][50][51][52][53][54][55][56][57][58] Indocyanine green (ICG), an ionic cyanine dye, has been approved by the U.S. Food and Drug Administration (FDA) for clinical NIR-I FLI. [59][60][61][62] Recently, ICG has also found application in clinical NIR-II imaging for guiding human liver cancer surgery as it has tail emission in this range.…”
Section: Introductionmentioning
confidence: 99%
“…[43][44][45][46][47] Among these OSMs, ionic cyanine dyes are extensively utilized in biomedical applications due to their exceptional photophysical properties including high extinction coefficient, intense NIR fluorescence, and excellent biocompatibility, attributed to their extensive conjugation structures involving two delocalized charged nitrogen atoms and polymethine chains. [48][49][50][51][52][53][54][55][56][57][58] Indocyanine green (ICG), an ionic cyanine dye, has been approved by the U.S. Food and Drug Administration (FDA) for clinical NIR-I FLI. [59][60][61][62] Recently, ICG has also found application in clinical NIR-II imaging for guiding human liver cancer surgery as it has tail emission in this range.…”
Section: Introductionmentioning
confidence: 99%
“…38,43,60,79,80 Merocyanine dyes are used in many applications such as photodynamic therapy, [81][82][83][84] upconverting nanoparticle technology 85,86 and plasmonic technology. 47,87,88 The main advantages of merocyanines are their high extinction coefficients, a significant change of the molecular dipole moment upon excitation, and the possibility to tune their spectral and luminescent properties by changing terminal donor and acceptor moieties and the polymethine chain length. 81 Here we study three (thio)barbiturate merocyanines, 89,90 whose plasmonic effect is easily observed and leads to significantly increased j fl .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, they can be used in the development of optoelectronic devices [4,5], nanolasers [6,7], and photodynamic therapy [8,9]. It was shown [10] that the addition of metal NPs to the active medium of dye lasers can lower their generation threshold. Also, in the presence of gold or silver NPs, the performance of solar [11][12][13] and photocatalytic [14][15][16] cells can be significantly increased.…”
Section: Introductionmentioning
confidence: 99%